2018
DOI: 10.1187/cbe.17-12-0258
|View full text |Cite
|
Sign up to set email alerts
|

Group Work

Abstract: This essay introduces an evidence-based teaching guide presenting research and resources related to group work. The guide provides links to key articles accompanied by summaries organized by teaching challenge and an instructor checklist. In addition to describing the guide, the article identifies areas for further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 12 publications
0
36
0
1
Order By: Relevance
“…Students have reported that they have been able to meet more of their peers and hear a greater diversity of perspectives than if they were placed in the same small group each class. In addition, the rotation of groups every class may increase individual accountability, a key aspect of successful group work (Wilson et al, 2018), if they will be paired with (and held accountable to) a random subset of their classmates.…”
Section: Advice For Implementati On Of This Modulementioning
confidence: 99%
See 2 more Smart Citations
“…Students have reported that they have been able to meet more of their peers and hear a greater diversity of perspectives than if they were placed in the same small group each class. In addition, the rotation of groups every class may increase individual accountability, a key aspect of successful group work (Wilson et al, 2018), if they will be paired with (and held accountable to) a random subset of their classmates.…”
Section: Advice For Implementati On Of This Modulementioning
confidence: 99%
“… Keep groups small and promote student engagement —the discussion‐based nature of the course is easier with a small class, but may be possible with larger classes as well. Even for larger classes, I do not recommend forming small groups above five students, since it may be more challenging to have each student participate equally in larger groups; past literature has suggested that small groups of three to five students tend to be the most effective (Wilson, Brickman, & Brame, 2018). If in the online format, I recommend asking each student to turn on their webcam (if available) to promote engagement. Rotate groups every class— even before the transition to online teaching, I had randomized groups every class, and I continued doing so with the online format using Zoom's random breakout groups feature.…”
Section: Advice For Implementation Of This Modulementioning
confidence: 99%
See 1 more Smart Citation
“…Mahasiswa mampu berkomunikasi dan diskusi interaktif dengan anggota lainnya meskipun tidak mengenal satu sama lain. Wilson menyatakan bahwa komunikasi efektif dapat meningkatkan kerja kolaborasi antar anggota (Wilson, Brickman, & Brame, 2018). Peneliti lain juga menyatakan bahwa komunikasi efektif dapat mendorong interaksi antar individu dalam kerja tim (Noguera, Guerrero-Roldán, & Masó, 2018).…”
Section: Gambar 3 Grafik Persebaran Mahasiswa Pada Tim Proyekunclassified
“…Nevertheless, teamwork requires social and intellectual collaboration that is not always easy for members to accept (16). Recent literature on science education strongly encourages undergraduate instructors to incorporate group work assignments into their classroom to allow students to build teamwork skills for their future careers (17). It is noteworthy that students in undergraduate programs often resist group work activities for a variety of reasons, such as competitiveness, difficulty relying on each other’s knowledge, and uneven division of responsibilities between team members (17).…”
Section: Introductionmentioning
confidence: 99%